1979
DOI: 10.1099/00221287-114-2-341
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Group P1 Plasmids Revealed by Heteroduplex Experiments: RP1, RP4, R68 and RK2 Are Identical

Abstract: The molecular relationships of the IncPl plasmids RPl, RP4, R68 and RK2 were tested by electron microscopic examination of heteroduplexes. In several hybridization experiments molecules were detected which had a 7.8% portion of incomplete reannealing. This ' heterologous region ' could be explained by the typical renaturation behaviour of the transposon Tnl. The identity of the Tnl transposon present in RP1 and RP4 was proved by heteroduplex experiments with h phage DNA containing this transposon. These result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(41 citation statements)
references
References 12 publications
0
40
0
Order By: Relevance
“…Nevertheless, studies focusing on the self-transmissible IncP plasmid RK2 (27) and the closely related plasmids RP1, RP4, R18, and R68 (9,84) have revealed a replicon of intriguing genetic and regulatory complexity (17,18,77).…”
mentioning
confidence: 99%
“…Nevertheless, studies focusing on the self-transmissible IncP plasmid RK2 (27) and the closely related plasmids RP1, RP4, R18, and R68 (9,84) have revealed a replicon of intriguing genetic and regulatory complexity (17,18,77).…”
mentioning
confidence: 99%
“…At such a copy number, it is likely that this plasmid encodes one or more elements responsible for ensuring its maintenance within the bacterial population (reviewed in references 2 and 29). Recent studies have shown that RK2 and the homologous isolate from Pseudomonas sp., RP4 (7), do contain information that promotes plasmid stabilization. A region within the PstI C fragment of these plasmids, from approximately 32.6 to 35.8 kb, has been shown to efficiently stabilize plasmids in a broad-host-range, vector-independent manner (18,31,33).…”
mentioning
confidence: 99%
“…Naturally occurring IncP elements (as illustrated by RK2, RP1, and R68 [1]) are large (>50 kb), stable, self-transferable plasmids which exist in four to seven copies per chromosome equivalent (7). The IncP plasmid consists of a contiguous block of conjugal transfer functions joined to a block of replication and maintenance functions.…”
mentioning
confidence: 99%